Arguments in favor of the extinction of the right of habitation due to the common-law relationship of the surviving spouse - Spirchez Georgeta-Bianca; Soptea Marius Cristian (Bulletin of the Transilvania University of Brasov, series VII: Social Sciences. Law. vol.17(66) no.1-2024, 2024)
As it is known, the remarriage of the surviving spouse causes the extinction of his right of habitation, a just regulation that takes into account the special and personal character of this right. However, we have raised the question of how to assess, in practice, the situation in which the surviving spouse did not remarry, but lives, in a common-law relationship in that house with another person. In this context, with this paper, we aim to give a legal and equitable solution to this problem.
Keywords: surviving spouse; habitation; common-law relationship